A Fast and Accurate Chirp Rate Estimation Algorithm Based on the Fractional Fourier Transform - Serbes, Ahmet; Aldimashki, Omair (IEEE, 2017)
In this work, a fast and accurate chirp-rate estimation algorithm is presented. The algorithm is based on the fractional Fourier transform. It is shown that utilization of the golden section search algorithm to find the maximum magnitude of the fractional Fourier transform domains not only accelerates the process, but also increases the accuracy in a noisy environment. Simulation results validate the proposed algorithm and show that the accuracy of parameter estimation nearly achieves the Cramer-Rao lower bound for SNR values as low as -7dB.
Keywords: Chirp signals; fractional Fourier transform; chirp rate; golden section search; SIGNALS; AMPLITUDE; DOMAIN; PHASE; Engineering; Telecommunications